Importing Coffee, Exporting Responsibility: A Postcolonial Analysis of the EU Deforestation Regulation in Rwanda - Von Glahn,Heléna Maria (2025)
This thesis investigates how deforestation is problematized within the European Union Deforestation Regulation (EUDR) and examines its implications for smallholder coffee producers in Rwanda. Drawing on Carol Bacchi’s ‘What’s the Problem Represented to Be?’ approach and postcolonial theory, the study analyzes how regulatory problem representations construct responsibility, knowledge, and compliance within global environmental governance by addressing the following research questions: How is the problem of deforestation represented in the EUDR? What implications and lived effects does this representation have for smallholder coffee farmers in Rwanda? Methodologically, the research employs a qualitative case study based on six semi-structured interviews with key stakeholders in Rwanda’s coffee sector, complemented by document analysis of the regulation itself and relevant policy literature. Findings reveal that the EUDR’s problem framing centers on agricultural expansion as the universal driver of deforestation and assumes uniform compliance capacity across contexts. However, interview data suggest that coffee production in Rwanda contributes minimally to forest loss and that structural constraints, such as limited digital infrastructure, financial capacity, and institutional support, render compliance disproportionately burdensome for smallholders. The thesis further highlights how the EUDR risks reinforcing global inequalities by imposing externally defined sustainability standards without adequate local consultation or support. It concludes by emphasizing the need for context-sensitive, inclusive implementation strategies. It proposes directions for future research on the socio-political impacts of transnational environmental regulation in low-deforestation, smallholder-dominated contexts.
Keywords: EUDR; Rwanda; deforestation; coffee value chain; international environmental governance; postcolonialism; WPR approach